ANALISIS TINGKAT STRESS WANITA KARIR DALAM PERAN GANDANYA DENGAN REGRESI LOGISTIK ORDINAL (Studi Kasus pada Tenaga Kerja Wanita di RS. Mardi Rahayu Kudus) - Nova, Nova; Ispriyanti, Dwi (MEDIA STATISTIKA, 2012)
Currently, the role of women has shifted from traditional to modern roles. From only a traditional role to bear children and run the household, women now have a social role which can be a career with supported higher education. This can result in conflict dual role as worker and housewife for women who have a family, so easy to cause stress. Several factors are thought to affect levels of stress, especially for career women is child care, housekeeping assistance, communication and interaction with children and husband, time for family, determining priorities, career pressures and family pressures, and the husband's view of the dual role of women. Based on the test independence of variables, seven variables have a relationship with the level of stress career woman.By using the likelihood ratio test and Wald test is found to be two factors affect the stress levels of women workers in Mardi Rahayu Kudus hospital are a time for family and the support of her husband in a career. Â  Keywords: Stress Level, Dual Role Conflict, Ordinal Logistic Regression, Mardi Rahayu Hospital.